A 23,000-year-old southern Iberian individual links human groups that lived in Western Europe before and after the Last Glacial Maximum. - Villalba-Mouco, Vanessa; van de Loosdrecht, Marieke S; Rohrlach, Adam B; Fewlass, Helen; Talamo, Sahra; Yu, He; Aron, Franziska; Lalueza-Fox, Carles; Cabello, Lidia; Cantalejo Duarte, Pedro; Ramos-Muñoz, José; Posth, Cosimo; et al. (Nat Ecol Evol, 2023)
Human populations underwent range contractions during the Last Glacial Maximum (LGM) which had lasting and dramatic effects on their genetic variation. The genetic ancestry of individuals associated with the post-LGM Magdalenian technocomplex has been interpreted as being derived from groups associated with the pre-LGM Aurignacian. However, both these ancestries differ from that of central European individuals associated with the chronologically intermediate Gravettian. Thus, the genomic transition from pre- to post-LGM remains unclear also in western Europe, where we lack genomic data associated with the intermediate Solutrean, which spans the height of the LGM. Here we present genome-wide data from sites in Andalusia in southern Spain, including from a Solutrean-associated individual from Cueva del Malalmuerzo, directly dated to ~23,000 cal yr BP. The Malalmuerzo individual carried genetic ancestry that directly connects earlier Aurignacian-associated individuals with post-LGM Magdalenian-associated ancestry in western Europe. This scenario differs from Italy, where individuals associated with the transition from pre- and post-LGM carry different genetic ancestries. This suggests different dynamics in the proposed southern refugia of Ice Age Europe and posits Iberia as a potential refugium for western European pre-LGM ancestry. More, individuals from Cueva Ardales, which were thought to be of Palaeolithic origin, date younger than expected and, together with individuals from the Andalusian sites Caserones and Aguilillas, fall within the genetic variation of the Neolithic, Chalcolithic and Bronze Age individuals from southern Iberia.